2023
DOI: 10.3389/fendo.2023.1256292
|View full text |Cite
|
Sign up to set email alerts
|

Canagliflozin alters the gut, oral, and ocular surface microbiota of patients with type 2 diabetes mellitus

Limin Wang,
Chenghong Liang,
Xiaojian Song
et al.

Abstract: BackgroundModifications in the gut microbiota may be a crucial factor in the efficacy of canagliflozin (Cana) in managing patients with type 2 diabetes mellitus (T2DM). However, the interplay between oral and ocular surface microbiota and this treatment remains poorly explored.AimThis study aimed to assess alterations in the gut, oral, and ocular surface microbiota pre- and post-Cana treatment in patients with T2DM.MethodsIn this 30-day, controlled before-and-after study, 21 treatment-naïve patients with T2DM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…It is increasingly recognized that the microbiome may affect the health and disease of the host [ 33 , 34 ]. Animal and clinical studies have shown that canagliflozin inhibits intestinal SGLT1, thereby altering the composition of the intestinal microbiota [ 17–19 , 35 , 36 ]. Our study also found canagliflozin-mediated changes in the gut microbiota in HSD-fed DSS rats.…”
Section: Discussionmentioning
confidence: 99%
“…It is increasingly recognized that the microbiome may affect the health and disease of the host [ 33 , 34 ]. Animal and clinical studies have shown that canagliflozin inhibits intestinal SGLT1, thereby altering the composition of the intestinal microbiota [ 17–19 , 35 , 36 ]. Our study also found canagliflozin-mediated changes in the gut microbiota in HSD-fed DSS rats.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that metformin alters the microbiome composition, but the microbiome is also a part of the mode of action of the drug and can modulate drug efficiency and toxicity [14][15] . Similarly to the firstchoice metformin, the action of novel glucagon-like peptide-1 receptor agonists (GLP-1-RA) and sodium-glucose cotransporter-2 inhibitors (SGLT-2i) toward the microbiome has been previously studied [16][17][18][19][20] . However, these studies have shown conflicting results regarding the changes in microbial diversity and abundance of microbial taxa.…”
Section: Introductionmentioning
confidence: 99%